The Rise of U.S. Antidumping Activity in Historical Perspective - Irwin, Douglas (Washington, D.C. : International Monetary Fund, 2005)
Empirical studies of antidumping activity focus almost exclusively on the period since 1980. This paper puts recent U.S. antidumping experience in historical context by studying the determinants of annual case filings over the past half century. The conventional view that few antidumping cases existed prior to 1980 is not correct, although most did not result in the imposition of duties. The increased number of cases in recent decades largely reflects petitions that target multiple source countries; the number of imported products involved has actually fallen since the mid 1980s. The annual number of antidumping cases is influenced by the unemployment rate, the exchange rate, import penetration (closely related to the decline in average tariffs), and changes in the antidumping law and enforcement in the early 1980s.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet